Applying EXCEL in Preparing Financial Statements of the Central Bengkulu Village Owned Enterprises - Saiful, Saiful; Nikmah, Nikmah (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2024)
Background: The objective of this community service is to improve the ability of BUMDes in preparing financial statements by applying excel. Contribution: The application of excel in the preparation of financial statements will contribute greatly to improve the quality of financial statements presented by BUMDes and have an impact on the effectiveness of decision making which ultimately supports the progress of these BUMDes. Method: The method for this community service are providing counseling on the importance of BUMDes financial reporting quality, provide counseling on effective identification on BUMDes transaction, provide technical guidance on the preparation of BUMDes financial statements using the Excel program, and discussion and Q&A on completely financial statement of BUMDes Results: BUMDes Damar Limo tourist trains and batik production as main business. Transactions that occur in these BUMdes include receipt of capital deposits, purchases of vehicles, equipment, raw materials, merchandise inventory, and supplies, payment of salaries and other costs, and revenue generation. The reports that must be presented include the income statement, statement of financial position, and statement of BUMdes health. Conclusion: The implementation of the Excel Accounting has an impact on presenting higher quality financial statements and managing BUMDes efficiently and professionally